Exploring Multifaceted Expectations from Teachers: An Analysis From Guardians’ and Students’ Perspective - Tabassum, Mayeesha; Alam, Md Mahbub-ul (Universitas Djuanda, 2024)
The teachers' role extends beyond academics, including sharing knowledge and imparting moral values and ethics to students. However, guardians and students have multi-dimensional expectations from their teachers, encompassing several facts and figures. Considering the context, this study investigates those multifaceted expectations aiming to bridge the gap and propose measures for enhancing the teachers' ability to meet the expectations of guardians and students. This study has collected data through a structured questionnaire survey. The sample population of this study includes guardians, students, and teachers from primary to tertiary education levels. A total of 384 samples were selected from unknown populations. A descriptive statistical technique (percentage analysis) was applied to identify patterns and trends in the quantitative data. This study finds that the expectations of guardians and students emphasize the teacher’s role as a good human being, guide, and role model. Skills for motivation, thirst for knowledge, empathy, and communication are considered the necessary qualities for an ideal teacher. Moreover, respondents argue that effective teacher-student relationships depend on fairness, openness, accessibility, and compassion. They emphasize enhancing teachers' humility, neutrality, clear communication, and ability to realize the expectations of students. The study recommends measures that may help teachers meet the intricate expectations of guardians and students, such as providing training, opportunities for higher education, ensuring academic support, teacher autonomy and flexibility, and depoliticizing educational institutions. It concludes that enhanced support and teacher training are vital in meeting the complex expectations of guardians and students. The findings of this study contribute to the enhancement of teaching-learning practices and the delivery of quality education